CREATIVE ISLAMIC TEACHING: A CPSS AND SOCIAL LEARNING APPROACH: English - Nur Intan; Arief Sah, Moh.; Syahid, Ahmad; Gusnarib (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
This study examines the teaching creativity of Islamic Religious Education (IRE) teachers at State Senior High School 4 Palu, specifically the teachers’ ability to generate novel ideas that are surprising yet comprehensible, and hold value in various aspects, using the Creative Product Semantic Scale (CPSS) framework and Albert Bandura’s social learning theory. Using a qualitative case study approach, data was collected through participatory observation, in-depth interviews with IRE teachers, the school principal, and document analysis. The data was analyzed interactively and validated through triangulation methods. The findings show that IRE teachers apply three CPSS indicators; novelty through innovative methods such as drill, gallery walk, number heads together, and the use of multimedia in the Tora Yaku and Ulul Albab IRE laboratories; problem-solving with collaborative projects and curriculum adjustments based on student needs; and elaboration and synthesis through the integration of Islamic concepts with real-life contexts. Additionally, institutional support, such as laboratory facilities and technology training, strengthens the teacher’s creative teaching practices. Bandura’s observational learning theory is evident in the modeling of teacher creativity, where students adopt innovative behaviors through observation, retention, and reproduction. Students’ self-efficacy increases through participatory methods like Numbered Heads Together and interactive discussions.